2010
DOI: 10.1007/s10822-010-9404-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and structural determinants of adamantyl susceptibility to HLA-DRs allelic variants: an in silico approach to understand the mechanism of MLEs

Abstract: Class II major histocompatibility complex (MHC II) molecules as expressed by antigen-presenting cells are heterodimeric cell-surface glycoprotein receptors that are fundamental in initiating and propagating an immune response by presenting tumor-associated antigenic peptides to CD4(+)/T(H) cells. The loading efficiency of such peptides can be improved by small organic compounds (MHC Loading Enhancers-MLEs), that convert the non-receptive peptide conformation of MHC II to a peptide-receptive conformation. In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 54 publications
3
10
0
Order By: Relevance
“…Finally, Table summarizes the affinity energy values computed by the MVD program for the TYR‐inhibitor complexes. Despite, the MOLDOCK scoring function not describing the relationship between the in silico and experimental data sufficiently well, it was found that the computed values are suitable for qualitative analysis in the case when multiple orientations are observed for the same compound. It is important to clarify that in the present work, the interest was only focused on predicting the position of the analogs within the active site of tyrosinase.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Table summarizes the affinity energy values computed by the MVD program for the TYR‐inhibitor complexes. Despite, the MOLDOCK scoring function not describing the relationship between the in silico and experimental data sufficiently well, it was found that the computed values are suitable for qualitative analysis in the case when multiple orientations are observed for the same compound. It is important to clarify that in the present work, the interest was only focused on predicting the position of the analogs within the active site of tyrosinase.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, MD simulations were conducted in order to see the possible effects of ximelagatran on the structure of the peptide binding groove of HLA-DRB1*07:01 and the conformation of bound ligand peptide, and to compare them with those of AdCaPy (one of the major histocompatibility complex loading enhancers [9]) and lapatinib [10]. The interaction modes of ximelagatran in the absence and presence of the ligand peptide were similar to those found in the docking study.…”
Section: Discussionmentioning
confidence: 99%
“…Ximelagatran binds along the center of the peptide binding groove of HLA-DRB1*07:01 and makes its deepest contact in or near the P4 pocket. In the absence of the ligand peptide, ximelagatran keeps the peptide binding groove in an open state (Figure 4d and Figure 5a) similarly to AdCaPy, which enhances the loading efficiency of ligand peptides onto several HLA-DR molecules [9]. However, unlike AdCaPy, which is small and interacts with the P1 pocket of HLA-DR molecules, ximelagatran interacts along a relatively large part of the peptide binding groove of HLA-DRB1*07:01.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to current molecular docking simulations (Table 3), certain docking studies analyzed modulation effects of additional molecules on the evaluated interaction [163165]. Homology modeling followed by extensive molecular dynamics simulation was used to identify nonpeptidic small organic compounds (among 150 000 compounds) that bind to a human leukocyte antigen HLA-DR1301, and block the presentation of myelin basic protein peptide (aa positions 152–165) to T-cells.…”
Section: Protein Dockingmentioning
confidence: 99%